A Novel 4-(1H-Benzimidazol-2-yl)-2-methoxy-phenol Derived Fluorescent Sensor for Determination of CN– Ion - Rahmawati, R.; Purwono, B.; Matsjeh, S. (Asian Journal of Chemistry, 2017)
A novel fluorescent sensor 4-(1H-benzimidazol-2-yl)-2-methoxy-phenol derivative was synthesized. Solution of 4-(1H-benzimidazol-2-yl)-2-methoxy-phenol (1 × 10–7 M) in DMSO displays highly sensitives and rapid respons to CN– ion [values of LOD = 1.8 × 10–6 M and Ka = 2.5 (± 0.26) × 106 M–1]. Sensor 4-(1H-benzimidazol-2-yl)-2-methoxy-phenol coordinated with CN– ion form with a 1:1 binding stoichiometry.